2019
DOI: 10.1111/1467-9604.12260
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion and SEN coaching: how accelerated learning and ‘workplace’ immersion can help develop core sport coaching skills

Abstract: In terms of best practice, the debate concerning SEN and disability sports coaching continues to be a contested area that many believe warrants further investigation (Townsend, Smith, and Cushion, 2015). Alongside this, higher education institutions (HEIs) in the UK continue to develop courses for sports coaches that emphasise reflection as a key component of student learning (Crisp, 2018). Through the use of a qualitative design and method, this study examines the use of a prolonged community engagement progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In the literature, it has been determined that the motoric development of the mentally handicapped is not sufficient, and it has been observed that the strength training applied to these individuals produces positive developments in their motoric properties [1,2,12,13,15]. When examined in this context, in the study conducted by Ates [30], in addition to the football training, there were significant differences in the results of vertical jump, leg and back strength, right hand grip strength, and sit-up test results in the football players who underwent plyometric training 2 days per week compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, it has been determined that the motoric development of the mentally handicapped is not sufficient, and it has been observed that the strength training applied to these individuals produces positive developments in their motoric properties [1,2,12,13,15]. When examined in this context, in the study conducted by Ates [30], in addition to the football training, there were significant differences in the results of vertical jump, leg and back strength, right hand grip strength, and sit-up test results in the football players who underwent plyometric training 2 days per week compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important concepts in disability sports is athletic success. In order to achieve a high level of success in sports, it is necessary to work systematically and based on training principles [11,12,13,14]. The idea of raising athletic performance to a higher level has appeared day by day in disability sports, and various training programs have been introduced.…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…The work of Jacobsen (2015) and Farrell and Van de Braam (2014), for instance, outlines how condensed programmes, qualifications, or education systems/ courses, allow for deeper, potentially more significant immersion and thus can compress learning. Of course, this is reliant on suitably appropriate and meaningful experiences and elicited responses, and the first author has outlined how coaching within the special educational needs (SEN) and disability context 'accelerated' a number of student-coaches' learning through facilitating educational and reflective transitions (Crisp, 2019b). However, whilst in the present study the application and/or use of accelerated learning to explain how the beginner-coaches developed some idea of what constitutes 'game sense' and in identifying appropriate training activities, we feel that simply having played sport may not be enough to facilitate coach learning.…”
Section: "I Feel That Because I Played Football I Am Now In a Better ...mentioning
confidence: 99%